Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content: 1. The relationship between educational capabilities and entrepreneurial performance A study on a sample of service sector establishments operating in the state of Khartoum, 2022 Dr. Hassan Abdul Rahim Fadl Muhammad, Dr. Sheikh Muhammad al-Khidr Muhammad, Dr. Hudhayfah bin Hadi Madkhali, Dr. Anis Muhammad Salih Souissi 2. The role of creative leadership in achieving institutional excellence Mr. Ahmed Hassan Alshekhi, D. Osama Abdul Rahman Mujallid 3. Unified legal regulation of bank interest and commissions - A comparative study between Islamic law and law – Mr. Haitham Ismail Muhammad Al-Baydani 4. Arbitration in public project disputes in the Law of Saudi Arabia Dr. Hashem Baker Alshaikh 5. The reality of the role of the Presidency of the Grand Mosque and the Prophet’s Mosque in managing the crisis under the COVID-19 pandemic is a model Mr. Tariq Khames Al-Zahrani 6. The Impact of the Work Environment on the Performance of Nurses in the Saudi Healthcare Sector Khaled Mansour Al-Thabeti, Amani Hassan Al-Dharawi, Haya Ali Al-Mabrouk, Abrar Fawaz Al-Fayez, Obaid Ali Al-Khairy, Ali Hassan Al-Rashdi, Belkhair Muhammad Abdullah, Badra Ibrahim Al-Zubaidi, Abdullah Ali Al-Khairy, Fares Suleiman Al-Jaloud 7. Technical Services for Organizing Crowds, Provided to Pilgrims, During Hajj Season Dr. Abdulaziz Mohammed Choudhry, Mr. Mansour Attia Al-Maliki, Mr. Wissam Walid Khurshid, Mr. Yasser Taj Shawli 8. Forensic accounting and the current state of the infrastructure components of its implementation Dr. Osama Issam Matar